1984
DOI: 10.1002/ijc.2910330117
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of fld‐3 friend erythroleukemia cellsin vitroandin vivo: Effect of89sr treatment and friend virus infection

Abstract: The effector cells from non-immunized mice capable of lysing 51Cr-labelled FLD-3 BALB/c Friend virus-induced erythroleukemia cells in vitro and cells capable of clearing FLD-3 cells labelled with 5-iodo-2'-deoxyuridine-125I (125IdUrd) from the lungs in vivo were characterized and compared with natural killer (NK) cells reactive against YAC-I lymphoma cells. Unlike NK cells, the cells capable of lysing FLD-3 cells in vitro were insensitive to antibodies directed against NK-2.1 or Thy-1.2 antigens (plus compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…During the early period after tumor onset (9 days) in immunized mice, splenic NK cell numbers increased even more profoundly to 40-60 times those found in unimmunized, leukemic mice (Currier and Miller, 2001;Miller et al, 1992), supporting the well-established fact that erythroleukemia antigens are powerful stimulants for NK cells (Afifi et al, 1986;Hagner, 1984;Iorio et al, 1986;Lust et al, 1984;Neri et al, 1989;Thurlow et al, 1986). In the bone marrow, however, NK cells increased only twofold, again demonstrating the resistance of bone marrow based cells (T, B, or NK) to the systemic presence of foreign antigens.…”
Section: Discussionmentioning
confidence: 81%
“…During the early period after tumor onset (9 days) in immunized mice, splenic NK cell numbers increased even more profoundly to 40-60 times those found in unimmunized, leukemic mice (Currier and Miller, 2001;Miller et al, 1992), supporting the well-established fact that erythroleukemia antigens are powerful stimulants for NK cells (Afifi et al, 1986;Hagner, 1984;Iorio et al, 1986;Lust et al, 1984;Neri et al, 1989;Thurlow et al, 1986). In the bone marrow, however, NK cells increased only twofold, again demonstrating the resistance of bone marrow based cells (T, B, or NK) to the systemic presence of foreign antigens.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to reactivity to allogeneic stem cells, NK cells are known to interact with autologous stem cells both in vitro and in vivo (23) . Thomson et al (24) reported that NK cells are capable of eliminating syngeneic stem cells in vivo after certain viral infections .…”
Section: Resultsmentioning
confidence: 99%
“…However, the leukemia, which is the subject of the present study, is known to be NK sensitive and T cell insensitive [47][48][49]. The tumor is non-responsive to the immunostimulants generated in vivo in the presence of poly I:C and, in fact, this leukemia appears to proliferate only in response to internal autocrine mechanisms [50,51], involving only epo and epoR.…”
Section: Discussionmentioning
confidence: 99%